Design and demonstration of a portable and low-cost Raman spectrometer for rapid and low-cost estimation of marker molecules in plants. Issue 8 (14th September 2022) - Sing, Dilip; Banerjee, Subhadip; Jana, Shibu Narayan; Mallik, Ranajoy; Ghosh Dastidar, Sudarshana; Majumdar, Kalyan; Bandyopadhyay, Amitabha; Kanti Haldar, Pallab; Sharma, Nanaocha; Mukherjee, Pulok K.; Bandyopadhyay, Rajib
Abstract: Quality assessment of medicinal, aromatic plants and plant parts, and spices are to large extent based on estimation of active molecules. Such estimations require high cost, time consuming and laboratory bound methods like High Performance Liquid Chromatography. These methods can handle very few samples at a time and have no portability. Raman spectrometer has been demonstrated to be useful in rapid detection and estimation of biological molecules that demonstrate Raman shifts. Hence, a relatively low cost and portable Raman spectrometer was designed with the commercially available components. The compatible software for its use like the graphical user interface and the calibration program were developed. With this spectrometer the Raman shifts obtained with the standard compounds—benzene, chloroform and glacial acetic acid, were quite compatible with the available standard reports. Then, piperine was estimated in black pepper ( Piper nigrum ) seed extracts and the coefficient of determination ( R 2 ) of 0.98 was obtained for the regression between the high performance liquidchromatography estimates and those based on the Raman spectrometer. The spectrometer can be used for other marker molecules in plants and their products by suitable modifications in the software.